Omotenashi as a hospitality value: A Sociopragmatic study of caddie communication in Japanese golf companies - Reny Wiyatasari; Farah Rizky Putri Dewati (Universitas Dian Nuswantoro, 2026)
Omotenashi, a fundamental Japanese cultural value, emphasizes genuine attentiveness, empathy, and the anticipation of guests' needs. In the golf industry, this value is epitomized by caddies, who serve as the primary interface of service. While research on Omotenashi has progressed across various disciplines, there remains a paucity of studies examining caddies' speech from a sociopragmatic perspective, particularly concerning language selection and communication strategies during direct guest interactions. This study seeks to explain the implementation of omotenashi culture at Japanese golf courses in various caddie service situations for guests, focusing on word choice, the use of keigo, and speech act strategies, as well as the reflection of omotenashi no kokoro values in caddies’ utterances when communicating with guests Data were collected through field notes documenting caddies' speech while accompanying guests during golf games, supplemented by interviews to elucidate the cultural considerations influencing their speech form choices. The analysis employed a sociopragmatic framework that connects linguistic form, speaker intent, and sociocultural norms. Although the company's training module provides a foundational guideline for service interactions, caddies exhibit linguistic adaptability based on the guest's status, age, social distance, and the communication context. The study's findings reveal a predominance of indirect and polite directive speech acts, accompanied by adaptive shifts in keigo levels, underscoring the strong value of Omotenashi no kokoro in fostering comfortable interactions. These findings affirm that Omotenashi within the golf industry is a dynamic and contextual communication practice, contributing to the advancement of sociopragmatic studies in Japanese services.